Improvement of Arterial Stiffness in the Transition From Acute Decompensated Heart Failure to Chronic Compensated Heart Failure. Issue 6 (12th April 2013) - Kim, Dong‐Bin; Baek, Sang Hong; Jang, Sung Won; Her, Sung‐Ho; Shin, Dong‐Il; Park, Chan Seok; Park, Hoon Joon; Kim, Pum Joon; Jung, Hae Ok; Seung, Ki Bae
Abstract Background Pulse wave velocity (PWV) is a well‐established marker for aortic stiffness and may be a prognostic factor in heart failure (HF). This study investigates whether PWV changes as patients transition from acute decompensated heart failure (ADHF) to chronic compensated heart failure (CCHF). Hypothesis Arterial stiffness is related with the development of HF. Methods Regional PWV was prospectively measured using noninvasive applanation tonometry in consecutive ADHF patients (n = 55). PWV measurements of 45 patients were taken at admission and 3‐month follow‐up (F/U). Results Central and upper‐extremity PWV, but not lower‐extremity PWVs, were found to have improved after 3 months compared with the admission PWV (central: 8.73 ± 1.17 vs 8.39 ± 0.99 m/s, P = 0.018; upper extremity: 8.59 ± 0.84 vs 8.33 ± 0.82 m/s, P = 0.028). Multivariate logistic regression analyses revealed that low‐density lipoprotein cholesterol was significantly associated with the change of PWV in HF (odds ratio: 1.037, 95% confidence interval: 1.003‐1.071, P = 0.030). In preserved left ventricular ejection fraction patients (n = 26) and ischemic patients (n = 31), central and upper‐extremity PWVs improved over the admission PWV at 3‐month F/U. Conclusions The present results indicate that central and upper‐extremity PWVs, but not lower‐extremity PWV, are increased in ADHF and improve as patients transition from ADHF to CCHF.